The effect of knowledge about halal and Islamic religiosity on attitude toward halal label - Hendy Mustiko Aji (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2018)
Halal label becomes the trend in Muslim lifestyle. It is aimed to separate halal from haram products. Muslim market is very huge. In Indonesia, Muslim dominating the total population approximately 80%. Many Muslims in Indonesia refused to purchase or consume the products that are not halal certified. Therefore, many believed that halal is a very huge business. Several previous researchers have already conducted study on what are the factors affecting attitude toward halal label. However, there are very few who researched Muslim’s knowledge about halal process and procedures and how it is affecting attitude toward halal label. Previous researchers also conducted the test on the effect of religiosity on attitude, however, most of them measure religiosity by Christian religiosity instrument. This research purposed to examine the effect of knowledge and Islamic religiosity on attitude toward halal label. There are 186 usable data that are dominated by male. Structural Equation Modeling (SEM) was used to test the model and hypotheses. It is found that knowledge has significant effect on Islamic religiosity and on attitude toward halal label. Interestingly, Islamic religiosity is not found significantly affecting attitude toward halal label.